World Development Report 2005 : A Better Investment Climate for Everyone - World Bank (World Bank, 2012)
Firms and entrepreneurs of all types from microenterprises to multinationals play a central role in growth and poverty reduction. Their investment decisions drive job creation, the availability and affordability of goods and services for consumers, and the tax revenues governments can draw on to fund health, education, and other services. Their contribution depends largely on the way governments shape the investment climate in each location through the protection of property rights, regulation and taxation, strategies for providing infrastructure, interventions in finance and labor markets, and broader governance features such as corruption. The World Development Report 2005 argues that improving the investment climates of their societies should be a top priority for governments. Drawing on surveys of nearly 30,000 firms in 53 developing countries, country case studies, and other new research, the Report explores questions such as: